CORPORATION OF STUDENTS' BASIC MATHEMATICS KNOWLEDGE FACULTY OF TARBIYAH AND TEACHING SCIENCEIAIS SAMBAS WEST KALIMANTAN - Abdul Wahab Syakhrani; Muhammad Ichsan Abda (Adisam Publisher, 2024)
The aim of the research is to determine the basic mathematical knowledge of each class and to find out the similarities or differences in basic mathematical knowledge of each class in the fifth semester of the Tarbiyah and Teacher Training Faculty at IAIS Sambas. The research method is a quantitative method. The research sample consisted of 104 people. The data collection technique uses Kruskal Wallis analysis. The research results showed that PGMI B class had the highest achievement percentage at 90%, followed by PGMI B at 87%, then PAI A class at 77%, followed by PAI B class at 72%, and finally PAUD class at 60%. The results of the Kruskal Wallis test show that there is a significant difference in basic mathematics knowledge of students from the Tarbiyah and Teacher Training Faculty at IAIS Sambas. However, it is hoped that students can continue to improve their abilities in mathematics, because very few can answer perfectly.